Amplified summer warming in Europe–West Asia and Northeast Asia after the mid-1990s. (8th September 2017) - Hong, Xiaowei; Lu, Riyu; Li, Shuanglin
Abstract: Regional temperature changes are a crucial factor in affecting agriculture, ecosystems and societies, which depend greatly on local temperatures. We identify a nonuniform warming pattern in summer around the mid-1990s over the Eurasian continent, with a predominant amplified warming over Europe–West Asia and Northeast Asia but much weaker warming over Central Asia. It is found that the nonuniform warming concurs with both the phase shift of the Atlantic Multi-decadal Oscillation (AMO) and the decadal change in the Silk Road Pattern (SRP), which is an upper-tropospheric teleconnection pattern over the Eurasian continent during summer. We suggest that the AMO may modulate the decadal change in SRP and then induce the zonal asymmetry in temperature changes. Our results have important implications for decadal prediction of regional warming pattern in Eurasia based on the predictable AMO.